ProBDNF Dependence of LTD and Fear Extinction Learning in the Amygdala of Adult Mice. (1st September 2021) - Ma, Xiaoyun; Vuyyuru, Harish; Munsch, Thomas; Endres, Thomas; Lessmann, Volkmar; Meis, Susanne
Abstract: Neurotrophins are secreted proteins that control survival, differentiation, and synaptic plasticity. While mature neurotrophins regulate these functions via tyrosine kinase signaling (Trk), uncleaved pro-neurotrophins bind preferentially to the p75 neurotrophin receptor (p75 NTR ) and often exert opposite effects to those of mature neurotrophins. In the amygdala, brain-derived neurotrophic factor (BDNF) enables long-term potentiation as well as fear and fear extinction learning. In the present study, we focused on the impact of mature BDNF and proBDNF signaling on long-term depression (LTD) in the lateral amygdala (LA). Hence, we conducted extracellular field potential recordings in an in vitro slice preparation and recorded LTD in cortical and thalamic afferents to the LA. LTD was unchanged by acute block of BDNF/TrkB signaling. In contrast, LTD was inhibited by blocking p75 NTR signaling, by disinhibition of the proteolytic cleavage of proBDNF into mature BDNF, and by preincubation with a function-blocking anti-proBDNF antibody. Since LTD-like processes in the amygdala are supposed to be related to fear extinction learning, we locally inhibited p75 NTR signaling in the amygdala during or after fear extinction training, resulting in impaired fear extinction memory. Overall, these results suggest that in the amygdala proBDNF/p75 NTR signaling plays a pivotal role in LTD and fear extinction learning.